Enhancing Students' Creativity and Social Studies Learning Outcomes through Discovery Learning - Nur Dwi Sukaruniawati; Muhammad Hanif; Yudi Hartono (Sakura Digital Nusantara, 2026)
Purpose: This study aims to enhance students' creativity and social studies learning outcomes through the implementation of the Discovery Learning model in Grade VII students. Methods: This study employed Classroom Action Research (CAR) conducted in two cycles at SMPN 14 Madiun during the 2025/2026 academic year. The participants consisted of 30 Grade VII students. Each cycle included the stages of planning, action, observation, and reflection. Data were collected through observation sheets to assess students' creativity and achievement tests to measure social studies learning outcomes. The data were analyzed using descriptive quantitative techniques based on percentage achievement and learning mastery. Findings: The results showed a significant improvement in students' creativity and social studies learning outcomes after the implementation of Discovery Learning. The percentage of students achieving good and very good creativity levels increased from the pre-cycle stage to Cycle II. Similarly, social studies learning mastery improved substantially, reaching complete learning mastery by the end of Cycle II. The findings indicate that Discovery Learning encourages students to actively construct knowledge, explore concepts, and engage in meaningful learning experiences. Research Implications: The findings imply that Discovery Learning can be effectively implemented as an instructional model to enhance students' creativity and social studies learning outcomes. The study provides practical guidance for social studies teachers in creating student-centered learning environments that promote active participation, creative thinking, and academic achievement. Originality: This study contributes to the existing literature by providing empirical evidence on the simultaneous improvement of students' creativity and social studies learning outcomes through the implementation of Discovery Learning within a Classroom Action Research framework. The study highlights the dual impact of Discovery Learning on both creativity and academic achievement in social studies learning.